Analysis and Inventory of Nahwu-Sharaf Materials in Juz ‘Amma for an Arabic Language Question Bank - Alfan Afifi Kurniawan; Sakinah Naziha (LPPM Universitas KH.A. Wahab Hasbullah, 2026)
This study aims to analyze and inventory nahwu (syntax) and sharaf (morphology) materials contained in the surahs from Surah Ad-Dhuha (Q.S. 93) to Surah An-Nas (Q.S. 114) as an empirical basis for developing an Arabic-language question bank. It responds to the limited availability of standardized, classified question banks for Arabic grammar and to the underuse of the Qur'an as a systematic source of authentic grammatical items. This research employed a descriptive-analytical qualitative method with a linguistic (content analysis) approach. Data were collected through critical reading, identification and selection of morphologically and syntactically distinctive words or phrases, and systematic tabulation, then verified through source triangulation using three classical i'rab references. The findings show 154 total entries: 101 sharaf entries (46 fi'il/45.5% and 55 isim/54.5%) and 53 nahwu entries spanning ten syntactic patterns. The most productive sharaf categories are isim masdar tsulasi and sifah musyabbahah/mubalaghah (11.9% each), while all mazid tsulasi verb patterns are represented. The dominant nahwu patterns are jumlah fi'liyyah (17.0%), followed by jumlah qasam and jumlah ismiyyah mubtada'-khabar (13.2% each). The study also identifies rare but pedagogically valuable tarkib constructions, such as dhamir fashl, istitsna' mufragha, man syarthiyyah, and taqdim khabar li al-hasr. These findings demonstrate that Juz 30 contains sufficient morphological and syntactic richness to serve as an authentic, structured, and pedagogically valuable source for a nahwu-sharaf question bank, and they suggest that item development should be staged according to grammatical category, textual familiarity, and construction complexity.